Approaches to the Treatment of Zero Equivalence in a Bilingual Dictionary - Vrbinc, Marjeta; Vrbinc, Alenka (Lexikos, 2017)
The article discusses the treatment of zero equivalence in an English–Slovene dictionary (ESD). The absence of equivalents in the TL is marked by two symbols: Ã˜ (a complete absence of any equivalent) and # (equivalence at the level of the entire message rather than at word level). Sixty-five lemmata in the ESD contain a slashed zero, a hash or both, but one and the same entry can contain more than one symbol. Detailed results are presented by parts of speech of the lemmata, starting with a numerical analysis, which is followed by analysis of the content of illustrative examples. Then follows a detailed discussion of lemmata expressing pragmatic meaning in the SL, lemmata with lexico-grammatical, grammatical and lexical differences between the SL and the TL as well as lemmata with a number of SL senses included under one sense in the ESD. In the ESD, the problem of zero equivalence is mostly solved by the inclusion of translated examples of use. Another method employed in the ESD is the use of short descriptions of the function of the lemma or one of its senses. In this way, a more successful and thorough retrieval of information can be achieved with every look-up.